Functional Heterogeneity of the Young and Old Duplicate Genes in Tung Tree (Vernicia fordii) - Jiang, Lan; Fan, Tingting; Li, Xiaoxu; Xu, Jun (Frontiers in Plant Science, 2022)
Genes are subject to birth and death during the long evolutionary period. Here, young and old duplicate genes were identified in Vernicia fordii. We performed integrative analyses, including expression pattern, gene complexity, evolution, and functional divergence between young and old duplicate genes. Compared with young genes, old genes have higher the values of Ka and Ks, lower Ka/Ks values, and lower average intrinsic structural disorder values. Gene ontology and RNA-seq suggested that most young and old duplicate genes contained asymmetric function. Only old duplicate genes are likely to participate in response to Fusarium wilt infection and exhibit divergent expression patterns. Our data reveals that young genes differ from old genes not only evolutionary properties, but also in their functional and structural. These results highlighted the characteristics and diversification of the young and old genes in V. fordii and provided a systematic analysis of these genes in the V. fordii genome.